2017
DOI: 10.1101/156646
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct epigenetic shift in a subset of Glioma CpG island methylator phenotype (G-CIMP) during tumor recurrence

Abstract: SUMMARYHistomorphology and current grading schemes are unable to predict glioma relapse and malignant tumor progression. We reported that the IDH-mutant associated Glioma-CpG Island Methylator Phenotype (G-CIMP) can be further divided into two clinically distinct subtypes independent of histopathological grading (G-CIMP-high and -low) with evidence of correlation with tumor progression. Here we performed a comprehensive epigenomic analysis of 74 longitudinally collected glioma samples (grade II-IV) to understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…Remarkably, the analysis of a small cohort of primary and recurrent matched tumor specimens, composed of LGG and GBM, revealed that some G-CIMP-high tumors exhibited a demethylated pattern after relapse that was similar to those observed in the G-CIMP-low gliomas, suggesting a progression from the G-CIMP-high to the G-CIMP-low subset 7 . Unpublished work from our own laboratory may provide further refinement of the epigenetic shift from G-CIMP-high to G-CIMP-low upon tumor recurrence in TCGA and non-TCGA specimens 73 . Interestingly, in that cohort, G-CIMP-low at recurrence appeared in 12% of all gliomas and shared epigenomic features resembling IDH-wildtype primary GBM 73 .…”
Section: G-cimp+ Subsets and Glioma Progression/recurrencementioning
confidence: 99%
See 4 more Smart Citations
“…Remarkably, the analysis of a small cohort of primary and recurrent matched tumor specimens, composed of LGG and GBM, revealed that some G-CIMP-high tumors exhibited a demethylated pattern after relapse that was similar to those observed in the G-CIMP-low gliomas, suggesting a progression from the G-CIMP-high to the G-CIMP-low subset 7 . Unpublished work from our own laboratory may provide further refinement of the epigenetic shift from G-CIMP-high to G-CIMP-low upon tumor recurrence in TCGA and non-TCGA specimens 73 . Interestingly, in that cohort, G-CIMP-low at recurrence appeared in 12% of all gliomas and shared epigenomic features resembling IDH-wildtype primary GBM 73 .…”
Section: G-cimp+ Subsets and Glioma Progression/recurrencementioning
confidence: 99%
“…Unpublished work from our own laboratory may provide further refinement of the epigenetic shift from G-CIMP-high to G-CIMP-low upon tumor recurrence in TCGA and non-TCGA specimens 73 . Interestingly, in that cohort, G-CIMP-low at recurrence appeared in 12% of all gliomas and shared epigenomic features resembling IDH-wildtype primary GBM 73 . Genome-wide decreases in DNA methylation levels associated with progression have also been reported by other studies 74,75 .…”
Section: G-cimp+ Subsets and Glioma Progression/recurrencementioning
confidence: 99%
See 3 more Smart Citations